2011
DOI: 10.1007/s10029-011-0890-1
|View full text |Cite
|
Sign up to set email alerts
|

Muscle degeneration in inguinal hernia specimens

Abstract: Background There are few articles in the literature reporting the histological changes of groin structures affected by inguinal hernia. A deeper knowledge of this matter could represent an important step forward in the identification of the causes of hernia protrusion. This study aimed to recognise the pathological modifications of muscular structures in autopsy specimens excised from tissues surrounding the hernia orifice. Methods Inguinal hernia was identified in 30 autopsied cadavers, which presented differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 15 publications
0
29
0
1
Order By: Relevance
“…It is well known the correlations between pharmacological strategies, such as in Crohn's disease, and the risk to develop rare tumors or complications such as bowel perforation. Bowel herniation also represents a risk factor of perforation (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Multiple Organ Failure (MOF) represents the fatal evolution of the peritonitis (4).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known the correlations between pharmacological strategies, such as in Crohn's disease, and the risk to develop rare tumors or complications such as bowel perforation. Bowel herniation also represents a risk factor of perforation (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Multiple Organ Failure (MOF) represents the fatal evolution of the peritonitis (4).…”
Section: Discussionmentioning
confidence: 99%
“…In literature, this feature is thought to be related to the static nature of the flat meshes which, incorporated by motionless and rigid tissue elements, impede the regular muscle function of the repaired groin . Furthermore, recent studies concerning the pathogenesis of hernia disease have demonstrated the degenerative source of inguinal protrusions . This has generated new interest in the search for a more physiological and pathogenetic consequent repair concept of inguinal hernias.…”
mentioning
confidence: 99%
“…As the inguinal region is one of the most motile areas of the body, it is surprising that all prosthetics used for hernia repair are static devices. Recent evidence indicates that inguinal hernia is a degenerative disease . Therefore, to repair abdominal wall defects, the goal of the employed therapy should be to regenerate typical abdominal wall tissue components.…”
mentioning
confidence: 99%